A theoretical review on the factors influencing the demand for park and ride facility - Syed Adnan, Sharifah Adibah Alyia; Kadar Hamsa, Abdul Azeez (2012)
The increasing dominance of the private vehicles as a mode of transport in Malaysia and declining in the use of public transport has created serious problems such as traffic congestion and inadequate parking spaces in the city centre. One of the measures to reverse this situation is to promote the use of public transport with adequate and affordable parking spaces at the public transportation terminal. Park and ride facilities were introduced in many areas as one of the transportation demand management strategies to encourage use of public transportation and at the same time to overcome the shortage of parking at the city areas. Park and ride facility can be described as a parking space with good connections to the public transport network where car drivers can park their cars and use public transport for some parts of their journey. This research aims to study the parking utilization pattern at the park and ride facility and factors influencing the demand for the park and ride facility at Putrajaya Sentral, Precinct 7. As an initial progress of this study, this paper highlights the literature review pertaining to the concept of park and ride and factors such as socioeconomic, travel and parking characteristics of the parking users that influence the use of the park and ride facility. Though the main focus of this paper addresses the analysis of literature on park and ride facility, formulation of objectives, methodology, and elements related to the initial stage of this study are also highlighted.